Silencing of Fused Toes Homolog (FTS) Increases Radiosensitivity to Carbon-Ion Through Downregulation of Notch Signaling in Cervical Cancer Cells - D.S., Prabakaran; Chaturvedi, Pankaj Kumar; Shimokawa, Takashi; Kim, Ki-Hwan; Park, Woo-Yoon (Frontiers in Oncology, 2021)
The effects of Carbon ion radiation (C-ion) alone or in combination with fused toes homolog (FTS) silencing on Notch signaling were investigated in uterine cervical cancer cell lines (ME180 and CaSki). In both cell lines, upon irradiation with C-ion, the expression of Notch signaling molecules (Notch1, 2, 3 and cleaved Notch1), γ-secretase complex molecules and FTS was upregulated dose-dependently (1, 2 and 4 Gy) except Notch1 in ME180 cells where the change in expression was not significant. However, overexpression of these molecules was attenuated upon silencing of FTS. The spheroid formation, expression of stem cell markers (OCT4A, Sox2 and Nanog) and clonogenic cell survival were reduced by the combination as compared to FTS silencing or C-ion irradiation alone. Additionally, immunoprecipitation and immunofluorescence assay revealed interaction and co-localization of FTS with Notch signaling molecules. In conclusion, FTS silencing enhances the radio-sensitivity of the cervical cancer cells to C-ion by downregulating Notch signaling molecules and decreasing the survival of cancer stem cells.